Screening of Foot Inflammation in Diabetic Patients by Non-Invasive Imaging Modalities - Nagase, Takashi; Sanada, Hiromi; Oe, Makoto; Takehara, Kimie; Nishide, Kaoru; Kadowaki, Takashi (IntechOpen, 2011)
None